Decane hydroconversion with Al–Zr, Al–Hf, Al–Ce-pillared vermiculites (2008)
A series of vermiculites pillared with mixed precursors of Al–Zr, Al–Hf and Al–Ce were obtained from natural vermiculite subjected to a process of negative charge reduction through hydrothermal treatment. The catalytic activity of the solids evaluated in the decane hydroconversion, was superior to that of recognized pillared clays and comparable to those of very active catalysts such as zeolites USY. The distributions of profiles of the reaction products suggest that the porosity/pore architecture of the pillared vermiculites should be similar to that of ultrastable Y zeolites.